Rural household income mobility in transitional China: Evidence from China Household Income Project - Sui Yang (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
Based on China Household Income Project rural data, this paper aims to study the changes of rural household income mobility in transitional China. The results show that with the economic reform and development, income mobility between 2007 and 2009 was much stronger than before. Regarding the structure of income mobility, the 'exchange mobility' is generally the major source, followed by the 'growth mobility'. The comparison with income inequality indicated that the low degree of mobility is not conducive to the narrowing of inequality. However, the high degree is not accompanied by the substantial reduction of income gaps either.
Keywords: D63; O15; R20; 330; income mobility; inequality; rural China